The Role Of Financial Literacy in Students in Ambon City - Nidia Soepriadi, Dewi (Journal of Management, 2024)
The purpose of this study is to look at the impact of financial literacy on investment decisions, which are moderated by financial behavior, among Ambon City students. This research takes a quantitative method. The sample population comprised 111 students from the Ambon City region. Primary data were gathered and analyzed using the Partial Least Squares method. The data was collected via a Likert Scale questionnaire distributed using Zoho Form utilizing the Purposive Sampling approach. According to the research findings, financial literacy has a strong favorable influence on investing decisions.